2016
DOI: 10.2147/ijgm.s119965
|View full text |Cite
|
Sign up to set email alerts
|

Multi-ethnic differences in HbA1c, blood pressure, and low-density-lipid cholesterol control among South Africans living with type 2 diabetes after a 4-year follow-up

Abstract: PurposeOur study set out to examine if disparities in control of glycated hemoglobin (HbA1c), blood pressure (BP), and low-density-lipoprotein cholesterol (LDL-C) existed among an urban multi-ethnic cohort of South Africans, living with type 2 diabetes mellitus (T2DM).Patients and methodsThis longitudinal, retrospective study consisted of 261 men and women with previously diagnosed T2DM who attended Charlotte Maxeke Johannesburg Academic Hospital, South Africa across two time periods 2009 and 2013. Demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 30 publications
(35 reference statements)
1
17
0
1
Order By: Relevance
“…Ethnicity is not considered as an independent risk factor for T2DM in this analysis, although individuals with either a mixed or black African ancestry have a greater risk due to their genetic predisposition. [22][23][24] The predicted T2DM risk of this study population may thus be an underestimation.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Ethnicity is not considered as an independent risk factor for T2DM in this analysis, although individuals with either a mixed or black African ancestry have a greater risk due to their genetic predisposition. [22][23][24] The predicted T2DM risk of this study population may thus be an underestimation.…”
Section: Discussionmentioning
confidence: 82%
“…It is, however, well known that individuals with either a mixed or black African ancestry have a greater risk of developing T2DM due to a presumed genetic predisposition. [22][23][24][25] It is thus noteworthy that the predicted T2DM risk of this study population is likely to be an underestimation. Despite this limitation, the current study identified an opportunity for interventional strategies towards T2DM risk reduction by targeting specific modifiable risk factors.…”
Section: Discussionmentioning
confidence: 87%
“…Low rates of control were notable among those with hypertension, hypercholesterolemia and diabetes, and comparable to prior estimates in South Africa. [ 39 , 40 ] The fact that such a small percentage of patients have well-controlled disease is not a surprise given that the study was performed in districts that are historically underserved. These findings further support the importance of the future HealthRise demonstration projects.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 21 studies, 5 were from South Africa(42)(43)(44)(45)(46), 5 from Ethiopia(11,(47)(48)(49)(50), 3 from Kenya (51-53), 2 from Tanzania (54, 55), 2 from Nigeria (56, 57), and 1 from Cameron (58), Uganda (59), Botswana(60), and Ghana(61). All studies were institution based cross-sectional studies.…”
mentioning
confidence: 99%
“…All studies were institution based cross-sectional studies. To de ne poor blood pressure control, BP cut point of ≥140/90 was used by 11 studies(11,43,47,48,50,53,(62)(63)(64)(65)(66), ≥140/80 by 3 studies(45,59,67) and ≥130/80 by 7 studies (44, 52, 54-56, 58) (Table 1).…”
mentioning
confidence: 99%